Structură psihică și specific familial - Mitrea, Georgeta (Calitatea Vieții, 1994)
The article is based on the premises of a complex relation existing between the social determinat on and the psychic features of the human personality. On the one hand, the social determination is able to create specific types of personality. On the other hand, the psychic life has her own determinism able to explain the psychic differentiations between people who are living within the same social context. The experience proves the existence of a difference between the social coordinates and the psychic life. The author had realised a research of more family types having been focussed on the views, evaluations and conclusions of the interrogated couples on their own families. The article presents just the results of those researches.